(untitled) (International Journal of Innovative Technologies in Economy, 2022)
People expect things to be more practical, quick, and simple as a result of developing societal changes. This has led to modifications to the spice products we regularly find on the market, which are created in instant form, especially in Indonesian delicacies whose spices are hard to get in some regions and whose cooking method is extremely laborious. Consequently, the objective of this service is to socialize and provide instruction on the production of instant spices using spices from the surrounding environment to PKK women so that they can produce superior goods in Gajahrejo village and improve the economy of coastal community.